Geopolitical Influence of Afghanistan’s Neighbors on the Country's Domestic and Foreign Policies - Wafa, Noorani; Mazloum Yar, Fayaz Gul (Devotion : Journal of Research and Community Service, 2024)
This paper examines the impact of Afghanistan’s neighbors on the country’s domestic and foreign policies. Afghanistan shares borders with Pakistan, Iran, China, India, and the Central Asian republics, and its unique geographical location has made it a focal point in regional and global geopolitics. Using a mixed-methods research approach that incorporates both quantitative and qualitative data, this study analyzes the economic, cultural, security, and political effects of Afghanistan’s neighboring countries on its policies. The findings reveal that economic and trade cooperation with China and Pakistan has contributed to Afghanistan’s infrastructure and economic development. Additionally, cultural and historical ties with Iran and India have played a significant role in strengthening Afghanistan’s political and social relationships. Furthermore, security and intelligence collaborations with Central Asian countries and China have helped mitigate security threats and promote regional stability. This research also proposes strategies to improve Afghanistan's relations and strengthen its domestic and foreign policies with its neighbors.